Pathological Features and Prognosis of Thymoma With or Without Myasthenia Gravis - Zhang, Yunfeng; Yu, Lei; Ke, Ji (Frontiers in Surgery, 2022)
Introduction: To evaluate the different pathological and clinical characters of thymoma with and without myasthenia gravis (MG) and to determine whether the presence of MG influences the prognosis in patients with thymoma. Methods: 425 consecutive patients operated was analyzed. A median sternotomy was used in 189 cases, and video-assisted thoracoscopic thymectomy was used in 236 cases. These patients with thymoma were subdivided into two groups: thymoma with myasthenia gravis MG (n=220) and thymoma without MG (n=205). All thymic epithelial tumors were classified according to the WHO histologic classification and the Masaoka clinical staging system. The result was evaluated according to the Myasthenia Gravis Foundation of America’s criterion. The clinical features of the 2 test were compared between the two groups, and the survival analysis of Cox treatment effects was compared between the two groups. Results: There were no perioperative deaths. The proportions of type A and thymic carcinoma were 0% in the group with MG and 10.7% (22/205) and 11.2% (23/205), respectively, in the group without MG. Thymic hyperplasia around the thymoma was 29.1% (64/220) in patients with MG and only 6.3% (13/205) in patients without MG (χ2=23.63, P=0.000). The overall survival curve showed that the 5-year and 10-year survival rates in the group without MG were 89.2% and 77.4%, respectively, while those in the MG group were 91.1% and 80.5%. Conclusions: The existence of MG has little influence on the prognosis of thymomas, but it is suitable for early diagnosis and treatment. Extended thymectomy should be performed on all patients with thymoma, whether they have MG or not.